DIRAS3, GPR171 and RAC2 were identified as the key molecular patterns associated with brain metastasis of breast cancer - Yan, Meidi; Sun, Haohang; Li, Guoqing (Frontiers in Oncology, 2022)
OBJECTIVE: Brain metastasis is a primary cause of morbidity and mortality in breast cancer patients. Therefore, elucidation and understanding of the underlying mechanisms are essential for the development of new therapeutic strategies. METHODS: Differential gene analysis was performed for those with and without distant metastasis in The Cancer Genome Atlas (TCGA) database and those with and without recurrence in the brain in the dataset GSE12276. The differentially expressed genes procured from the two databases were intersected to obtain the intersecting genes associated with brain metastasis. Thereafter, the intersecting genes were subjected to LASSO model construction to screen for prognostic genes. The expression of the obtained genes in metastatic breast cancer was observed, and survival analysis was performed. Finally, GSEA analysis of the obtained genes was performed, and the relationship between them and immune cells was explored. RESULTS: A total of 335 differential genes for the occurrence of distant metastases were obtained based on the TCGA database. A total of 1070 differential genes for recurrence to the brain were obtained based on the dataset GSE12276. The Venn diagram showed 24 intersecting genes associated with brain metastasis. The LASSO prognostic model contained a total of five genes (GBP2, GPR171, DIRAS3, RAC2, and CACNA1D). Expression difference analysis showed that GBP2, GPR171, DIRAS3, and RAC2 were significantly down-regulated in expression in metastatic breast cancer compared with primary breast cancer tumors. Only GPR171, DIRAS3, and RAC2 were strongly correlated with the overall survival of breast cancer patients. Their correlation analysis with immune cells showed that the correlation coefficient between the expression levels of DIRAS3 and immune cells was low, and the expression levels of GPR171 and RAC2 were more closely correlated with B cells and macrophages. CONCLUSIONS: The expression of DIRAS3, GPR171 and RAC2, genes associated with brain metastasis, was reduced in metastatic breast cancer, and GPR171 was found to promote brain metastasis of breast cancer cells by inducing B cells and thereby.